Brain Derived Neurotrophic Factor in Pregnancy: Stress Responses and Fetal Neurodevelopment: BDNF in Pregnancy - Afridi, Aafia; Adam, Mohammedelfateh; Pathan, Soobia; Ali, Karam; Ahsan, Naveed; Sarwer, Aneela; Ali, Akram (Pakistan Journal of Health Sciences, 2024)
BDNF was a protein that has crucial role in development of brain in fetuses however its levels were affected by maternal stress response that cause complications. Objective: To study the effects of Brain Derived Neurotrophic Factor (BDNF) in stress response during pregnancy on developing fetus in order to bring clinicopathological correlations. Methods: As PRISMA guidelines suggested, an extensive database search was made from PubMed, Science Direct, and Google Scholar for articles that were released between 2016 and 2024. Included studies analyzed differences in BDNF as a function of maternal stress responses expressed by increased levels of maternal stress activity and changes in maternal brain. This review also included fetal neurodevelopmental issues which related to brain development and stress biomarkers. Google Scholar was used for 60% of the articles with various locations. Results: The review also revealed strong relations between high levels of BDNF and mothers’ stress reactions that included tangible changes in cortisol levels and some parts of the brain as the amygdaloid complex. The effect of maternal stress was observed to be regulated through alteration of brain plasticity by BDNF. Additionally, maternal BDNF concentration has been associated with the changes in fetal brain development such as modifications in brain weight and stress related biomarkers in cord blood serum samples. Conclusions: Maternal stress was hence a critical driver of neurodevelopmental outcomes of fetuses and newborns through BDNF. If implemented, this information may help to understand how BDNF regulates the types of stresses that a mother experiences along with fetal brain development.